The effect of tofacitinib on residual pain in patients with rheumatoid arthritis and psoriatic arthritis - Dougados, M; Taylor, P; Bingham III, CO; Fallon, L; Brault, Y; Roychoudhury, S; Wang, L; Kessouri, M (BMJ Publishing Group, 2022)
Objective: Post hoc analysis of pooled data from 9 randomised controlled trials to assess the effect of tofacitinib (oral Janus kinase inhibitor for treatment of rheumatoid arthritis [RA] and psoriatic arthritis [PsA]) on residual pain in patients with RA or PsA with abrogated inflammation.